2018
DOI: 10.1515/sjecr-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Molecular Adsorbent Recirculating System (MARS) in the Treatment of Acute Liver Failure (ALF) Case Report

Abstract: Acute liver failure (ALF) is a rare but life-threatening illness with multiple organ failure. The short-term mortality rate exceeded 80 % despite modern approaches in treatment. Drugs, infections by hepatic viruses and toxins are the most common causes of ALF. Progressive jaundice, coagulation disorder and hepatic encephalopathy are dominated as a clinical signs of the illness. We present a case of a 36-year-old Caucasian woman hospitalized in ICU due to yellow discoloration of the skin and sclera, severe diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…It was successfully used for the first time in the treatment of ALF as part of acute hepatitis B infection (15). A review of the literature has shown that MARS is an effective treatment for intractable pruritus with a significant decrease in the bilirubin and bile acid levels after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…It was successfully used for the first time in the treatment of ALF as part of acute hepatitis B infection (15). A review of the literature has shown that MARS is an effective treatment for intractable pruritus with a significant decrease in the bilirubin and bile acid levels after the procedure.…”
Section: Discussionmentioning
confidence: 99%